A note-restructuring intervention increases students’ exam scores - COHEN, Dov (Institutional Knowledge at Singapore Management University, 2013)
It was hypothesized that students’ learning would be enhanced by an intervention getting them to elaborate on and restructure the notes they had taken in lecture. Students in a research methods course were randomly assigned to weeks in which they would turn in a copy of their restructured lecture notes along with a very brief summary of the class. This intervention required students to spend quality time-on-task. Subsequently, results of exam questions from weeks in which students completed the intervention were compared to weeks they did not do so. The intervention improved student performance by a full class grade (11 percent, effect size d = 1.1) and it improved performance equally for students at the top, bottom, and middle of the class.